2020
DOI: 10.3390/molecules25040831
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Natural (−)-Antrocin and Its Enantiomer via Stereoselective Aldol Reaction

Abstract: The total synthesis of (−)-antrocin and its enantiomer are presented. Antrocin (−)-1 is an important natural product which acts as an antiproliferative agent in a metastatic breast cancer cell line (IC50: 0.6 μM). The key features of this synthesis are: (a) selective anti-addition of trimethylsilyl cyanide (TMSCN) to α,β-unsaturated ketone; (b) resolution of (±)-7 using chiral auxiliary L-dimethyl tartrate through formation of cyclic ketal diastereomers followed by simple column chromatography separation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…More energetic conditions showed instead a mixture of enolates in accordance with their thermodynamic stability, as reported in the literature (Scheme 1c). 3,15 In light of this evidence, the synthesis of natural (−)-antrocin via regioselective aldol reaction, recently published by Angamuthu et al, 16 captured our attention and fed our curiosity. The authors reported a kinetic-controlled aldol addition on cyclic ketone 4, functionalized in the β-position with an aldehyde group, as a key step for the regio-and stereo-selective synthesis of lactol (+)-II (Scheme S5 †).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…More energetic conditions showed instead a mixture of enolates in accordance with their thermodynamic stability, as reported in the literature (Scheme 1c). 3,15 In light of this evidence, the synthesis of natural (−)-antrocin via regioselective aldol reaction, recently published by Angamuthu et al, 16 captured our attention and fed our curiosity. The authors reported a kinetic-controlled aldol addition on cyclic ketone 4, functionalized in the β-position with an aldehyde group, as a key step for the regio-and stereo-selective synthesis of lactol (+)-II (Scheme S5 †).…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, the authors reported that the same cyclic substrate with a cyano group in the β-position (ketone 5) gave "kinetic product" 5b as main enolate under same conditions with a regioselectivity of 70 : 30 over the "thermodynamic product" 5a (Scheme S6 †). 16 Unfortunately, no explanations were given by the authors to elucidate the reverse selectivity and unexpected reactivity under the same kinetic conditions (Schemes S5 and S7 †). In recent years, theoretical studies on the deprotonation of symmetrical and unsymmetrical ketones have aroused great interest, 17 but most of them are focused on α-substituted ketones 18,19 and unsubstituted ketones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the total synthesis of natural (−)-antrocin ( 187 ) and its enantiomer has been reported [ 176 ]. Despite remarkable antitumor activities, the difficulties to prepare (−)-antrocin ( 187 ) triggered researchers to find a synthetic alternative.…”
Section: Biological Activities and Chemistry Of Natural And Synthementioning
confidence: 99%
“…Next, α -hydroxymethylation of (+)- 301 by reacting with lithium enolate with gaseous formaldehyde in THF yielded a single lactol (+)- 302 . The authors proposed that this reaction is controlled kinetically [ 176 ]. Lactol ( 302 ) was then oxidized with silica-supported pyridinium chlorochromate (PCC) to give lactone (−)- 303 .…”
Section: Biological Activities and Chemistry Of Natural And Synthementioning
confidence: 99%